Pembangunan Daftar Kata Terkait pada Kosa Kata Al-Qur'an Berdasarkan Kesamaan Distribusiaonal - Fedy Fahron Guntara (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2020)
The Quran is the Muslim holy book that contains so many words in it. This makes it difficult for ordinary people to find connections between words in the Quran. For example like the word مَّعْرُوف which has a connection with the word عَفَا because in the Quran the two words are often in one verse and also the two words have a connection in the meaning of forgiving is one of the good deeds. At present, there is no dictionary, encyclopedia or thesaurus in the vocabulary of the Quran that explains the interrelationships of words in the Quran. Therefore this study will discuss a connection with the words in the Qur'an and to further assist in finding the interrelations between verses. The method used in this study is a method with a distribution-based equality approach based on Continuous Bag of Word (CBOW). The use of the CBOW method produces a precision value of 98% based on the results of the system output with the correction from linguists